A prototype for data integration between case tools - Pereira, Marcelo Zilio (2002)
his paper presents a solution for data integration between CASE (Computer Aided Software Engineering) tools by using XML (eXtensible Markup Language) documents. The propose makes possible the conversion of an XML document, generated by one CASE tool, in another XML document, that can be read by another CASE tool. To make this conversion possible it is necessary to read sample XML documents from each CASE tool, associate their equivalent structures, generate a transformation script, and finally execute the conversion. In this work we present the specifications, the architecture and the implementation of a prototype (named InterCASE) that supports the XML conversion between CASE tools.